1970
DOI: 10.4314/ahs.v19i4.19
|View full text |Cite
|
Sign up to set email alerts
|

High risk human papillomavirus (HPV) common among a cohort of women with female genital mutilation

Abstract: Background: Nigeria accounts for 25% of cases of Female genital mutilation (FGM) worldwide, with increased incidence of cervical cancer.Objective: This study was aimed at evaluating the relationship between FGM and HPV in a locality with high prevalence of FGM.Methods: Papanicolaou test, DNA hybridization using Polymerase Chain Reaction (PCR), and flow-through hybridization was done to determine the genotypic variants of the HPV. Physical examination and questionnaires were also used to ascertain presence of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…Data were collated from studies conducted between 2004 [18] and 2019 [13,[19][20][21][22]. Except for the southeastern region of Nigeria where there were no data generated, all HPV genotyping of Nigerian participants were conducted in laboratories in North-central [15,16,20], North-east [23], North-west [15,22] and South-west [13,14,17,18,24] and South-south [25].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Data were collated from studies conducted between 2004 [18] and 2019 [13,[19][20][21][22]. Except for the southeastern region of Nigeria where there were no data generated, all HPV genotyping of Nigerian participants were conducted in laboratories in North-central [15,16,20], North-east [23], North-west [15,22] and South-west [13,14,17,18,24] and South-south [25].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One study was conducted in 200 women between 15 and 60 years old in Nigeria. Despite potential confounding factors, 78.3% of HPV infections were found among the 98 women with FGM/C 12,13 . Another study on 2398 women between 18 and 90 years old was conducted in Senegal.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies concluded that further research is needed, particularly regarding the role of other risk factors for cervical dysplasia associated with FGM/C and of different types of cutting. They indeed acknowledged that not differentiating the four types of cutting was a limitation 12,13 . A case–control study on risk factors of invasive cervical cancer from Mali, a country where FGM/C is highly prevalent, included 82 cases and 97 controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 FGM is also associated with a reduced level of antenatal care 12 and other health-care service utilization 13,14 and increases the risk of Human papillomavirus infection. 15 Despite many physical, sexual, and psychological problems are associated with FGM, it is still practiced in greater than 30 countries mainly in the west and east Africa including Ethiopia. 2 United Nations Population Fund (UNFPA) and the United Nations Children's Fund (UNICEF) have a program focusing on empowering women through education, community discussion, and national commitments to abandon FGM practice.…”
Section: Introductionmentioning
confidence: 99%